Off-Pump Coronary Artery Bypass Graft (OCABG) Surgery Outcome: AKI Incidence, Serum Uric Acid, and Cut-Offs of Variables - Mohamad Reza Zare-Khormizi; Fatemeh Pourrajab (Hindawi-Wiley, 2024)
Conclusion: SUA levels are independently associated with a higher risk of AKI and outcome complications after off-pump CABG, and confounding factors at specific cutoffs affect the odds ratio of UA for AKI occurrence.